Protective Role of Matrix Metalloproteinase-2 in Allergic Bronchial Asthma - Takahashi, Yoshinori; Kobayashi, Tetsu; D'Alessandro-Gabazza, Corina N.; Toda, Masaaki; Fujiwara, Kentaro; Okano, Tomohito; Fujimoto, Hajime; Asayama, Kentaro; Takeshita, Atsuro; Yasuma, Taro; Nishihama, Kota; Inoue, Ryo; et al. (Frontiers in Immunology, 2019)
Inflammation, reversible obstruction and hyperresponsiveness of the airways are characteristic findings of bronchial asthma. Several evidence has demonstrated the involvement of matrix metalloproteinase-2 in allergic airway inflammation. Matrix metalloproteinase-2 may promote aberrant tissue remodeling in late stages of allergic airway inflammation. However, whether matrix metalloproteinase-2 is detrimental or protective in early stages of allergic airway inflammation remains unclear. To evaluate this here we compared the severity of allergic bronchial asthma between mice overexpressing human matrix metalloproteinase-2 and wild type mice. After sensitization and challenge with an allergen, mice overexpressing the human matrix metalloproteinase-2 showed a significant reduction in airway hyperresponsiveness and in the expression of Th2 cytokines and IgE compared to their wild type counterparts. An inhibitor of matrix metalloproteinases abolished this beneficial effect of human matrix metalloproteinase-2 overexpression. Allergen-sensitized and challenged human matrix metalloproteinase-2 transgenic mice had enhanced percentage of M1 macrophages with increased expression of inducible nitric oxide synthase and STAT1 activation in the lungs compared to their wild type counterparts. There was no difference in the percentage of regulatory T cells between mouse groups. The results of this study showed that matrix metalloproteinase-2 is protective in allergic bronchial asthma by promoting polarization of macrophages to M1 phenotype.